A randomized controlled trial to assess the influence of a picture-based antiemetic medication calendar on medication-taking behavior in adults receiving chemotherapy. (December 2022) - Maximos, Mira; Smith, Kelly; Harris, Venita; McFarlane, Thomas; Blay, Jonathan; Hahn, Karin; Chang, Feng
Objective: A prospective open-label randomized controlled trial to assess the role of a picture-based medication calendar on adherence to antiemetic regimens for adult patients receiving chemotherapy and assess the effect on other medication taking behaviors as well as patient satisfaction with the tool. Methods: Participants were randomly assigned 1:1 to routine care with or without calendar. Results: Adherence, stratified by education (university or postgraduate, p = 0.09; grade school, high school or college p = 0.32), was non-significantly different between study arms. At least 70% of intervention arm participants moderately or completely agreed that the calendar helped with medication taking behaviors. There was no statistical difference between study arms for perceived regimen complexity ( p = 0.16). Medication Use and Self Efficacy score (adjusted for age) used to assess perceived self-efficacy with medication taking behaviors were not statistically significant between study arms ( p = 0.09). Conclusion: The picture-based medication calendar did not statistically affect adherence to scheduled antiemetics among outpatients receiving chemotherapy for solid organ tumor origins. However, participants indicated that the calendar was effective for keeping track of medications, had an easy-to-understand layout, and provided help around when and how to take medications related to the oncology regimen.